The Interspersian Index as a Technique for Evaluation of Bobwhite Quail Habitat - William L. Baxter; Carl W. Wolfe (National Quail Symposium Proceedings, 2017)
An index based on the interspersion of vegetative types proved useful in evaluating quail habitat. Application of the technique for related studies indicated that interspersion indices may find wider application for assessing habitat deficiencies, for evaluating land areas for production of a diversity of wildlife species, and for planning.